Demystifying the Aquatic Paradox: The Infant Mortality in India. (September 2020) - Banerjee, Subhanil; Singh, Anukriti; Bhattacharya, Sumantra; Koner, Souren
It is evident that better access to improved water sources will lead to the lessening of infant mortality rate (IMR). However, for India, such inference is ambiguous. There is a strong group of academicians such asSahu et al. (2015), Arun et al. (2017) andTripathy and Mishra (2017) and organizations such as UNICEF that firmly believe that if access to the improved water sources can be improved, then there would be tremendous social welfare and much betterment to the IMR. On the other hand, Banerjee et al. (2020) have refuted such claims and opined that access to improved water sources increases the IMR. The empirical validation of their claim has been flawless, but they are somewhat silent on why such a direct relationship between IMR and improved water source exists. They have made a comment based on assumptions that it might be complacency that develops with access to improved water sources that refrain the people to consider any type of water treatment before passing it to infants for drinking. Such a comment might be valid, but neither is it built upon a sound literature review nor does it stand on strong empirics. At this juncture, the present article tests the claim ofBanerjee et al. (2020) based on pure empirics.